Genotypes and haplotypes of the VEGF gene are associated with higher mortality and lower VEGF plasma levels in patients with ARDS. Issue 8 (8th February 2007) - Zhai, R; Gong, M N; Zhou, W; Thompson, T B; Kraft, P; Su, L; Christiani, D C
Abstract : Background: Endothelial injury is an important prognostic factor in acute respiratory distress syndrome (ARDS). Vascular endothelial growth factor (VEGF) plays a critical role in endothelial destruction and angiogenesis. Genetic variations of the VEGF gene have been associated with VEGF production. A study was undertaken to investigate the impact of VEGF gene polymorphisms on the clinical outcomes of ARDS. Methods: Three VEGF polymorphisms (−460C/T, +405C/G and +936C/T) were determined in 1253 patients in an intensive care unit with risk factors for ARDS, 394 of whom developed ARDS. Patients were followed for assessment of 60 day survival. Plasma VEGF levels were measured in 71 patients with ARDS. Results: The +936TT (OR 4.29, 95% CI 1.12 to 16.40, p = 0.03) and +936CT+TT (OR 1.98, 95% CI 1.14 to 3.42, p = 0.01) genotypes were significantly associated with increased mortality from ARDS. Plasma VEGF levels in patients with ARDS with the +936CT+TT genotype were significantly lower than in subjects with the +936CC genotype (median 49 (IQR 16–98) pg/ml vs 112 (IQR 47–162) pg/ml, p = 0.02). At the haplotype level, haplotype TCT (−460T+405C+936T ) was significantly associated with a higher rate of mortality (OR 2.89, 95% CI 1.30 to 6.43, p = 0.009) and haplotype CGT (−460C+405G+936T ) was associated less strongly with increased mortality (OR 1.90, 95% CI 0.94 to 3.83, p = 0.07) in patients with ARDS. Lower plasma VEGF levels were correlated with the probability of haplotype CGT (coefficient = −0.26, p<0.05), but the same trend of correlation was not significant to haplotype TCT . Conclusions: VEGF polymorphisms may contribute to the prognosis and inter-individual variations in circulating VEGF levels in patients with ARDS.